Population Pharmacokinetic Analysis for Imipenem–Relebactam in Healthy Volunteers and Patients With Bacterial Infections. (4th October 2019) - Bhagunde, Pratik; Patel, Parul; Lala, Mallika; Watson, Kenny; Copalu, William; Xu, Ming; Kulkarni, Pooja; Young, Katherine; Rizk, Matthew L.
Abstract : Relebactam is a small‐molecule β‐lactamase inhibitor developed as a fixed‐dose combination with imipenem/cilastatin. The pharmacokinetics of relebactam and imipenem across 10 clinical studies were analyzed using data from adult healthy volunteers and patients with bacterial infections. Renal function estimated by creatinine clearance significantly affected the clearance of both compounds, whereas weight and health status were of less clinical significance. Simulations were used to calculate probability of joint target attainment (ratio of free drug area under the curve from 0 to 24 hours to minimum inhibitory concentration (MIC) for relebactam and percentage of time the free drug concentration exceeded the MIC for imipenem) for the proposed imipenem/relebactam dose of 500/250 mg, with adjustments for patients with renal impairment, administered as a 30‐minute intravenous infusion four times daily. These dosing regimens provide sufficient antibacterial coverage (MIC ≤ 4 μg/mL) for all renal groups.